Using technology for formative assessment in food preservation learning - Nani Yuliani; Yatti - Sugiarti; Dwi Lestari Rahayu (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2020)
Abstract The research aims to determine the cognitive and affective aspects of learning outcomes on food preservation learning that applies formative assessment using Plickers app. The study used quasi experimental method with non equivalent control group design. The research sample consisted of 22 students as an experimental class and 22 students as a control class. Measurement of learning outcomes of cognitive aspects was based on the reults of the pretest and posttest. Measurement of learning outcomes for affective aspects was based on the results of assessment of indicators of visual, verbal, listening, drawing, writing, motor, mental, and emotional activity. The results showed that the experimental group that implemented formative assessment using the Plickers app had cognitive learning outcomes better than the control class. The average score of the N-Gain experiment class was 0.486 (in the medium category), while the control class was 0,266 (in the low category). The average results of the indicators assessment of affective aspects on the experiment class was in a very good category whereas the control class was in a good category. Applying formative assessments with the Plickers app not only provides assessments but also increases student learning activities and involvement in the learning process. Penilaian formatif menggunakan teknologi pada materi pengawetan bahan panganPenelitian ini bertujuan untuk mengetahui hasil belajar pada aspek kognitif dan afektif siswa pada pembelajaran materi pengawetan bahan pangan yang menerapkan formative assessment menggunakan aplikasi Plickers. Penelitian menggunakan quasi experimental method dengan non equivalent control group design. Sampel penelitian terdiri dari 22 siswa sebagai kelas eksperimen dan 22 siswa sebagai kelas kontrol. Pengukuran hasil belajar aspek kognitif dilakukan berdasarkan hasil pre-test dan post-test. Pengukuran hasil belajar aspek afektif didasarkan pada hasil penilaian indikator aktivitas visual, lisan, mendengarkan, menggambar, menulis, motorik, mental, dan emosional. Hasil penelitian menunjukkan bahwa kelas eksperimen yang menerapkan formative assessment menggunakan aplikasi Plickers memiliki hasil belajar pada aspek kognitif yang lebih baik dari kelas kontrol. Nilai rata-rata N-Gain kelas eksperimen adalah 0,486 (kategori sedang) sedangkan pada kelas kontrol adalah 0,266 (kategori rendah). Rata-rata penilaian indikator hasil belajar aspek afektif kelas eksperimen berada pada kategori sangat baik sedangkan kelas kontrol berada pada kategori baik. Penerapan penilaian formatif dengan aplikasi selain memberikan penilaian juga meningkatkan aktivitas belajar dan keterlibatan siswa.